The Pendampingan Transformasi Desa Tangguh Bencana (Destana) Pratama Menuju Utama Desa Klungkung Kabupaten Jember Tahun Ke-II: - - Mulyono, Joko; Arifiyanti, Jati; Paramitha, Nurina Adi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: The paradigm of disaster management has changed from a responsive view to an anticipatory one. The organization/institution and work program of Destana Desa Klungkung which was formed since 2018 has not been running optimally, while in Klungkung Village there are many potential disasters such as floods, landslides, droughts, and fires. The title of Pratama Disaster Resilient Village is still not powerful enough. The urgency of this community service program is so that Destana can be more useful in carrying out disaster prevention, so that disasters can be anticipated, their risks reduced, and they can be managed properly. The purpose of the community service program from year I to year III (2023-2025) is to strengthen the Destana institution through assistance in preparing disaster management programs and implementing programs, as well as assistance in exit strategies for terminating the program. Method: Activities consist of mentoring and compiling Disaster Identification Documents, Risk Analysis on Assets, Determination of Policies and Strategies, Disaster Contingency Plan (RKB) documents, including Projections of Planning and Needs between Operational Fields, and compiling Disaster Management Plan (RPB) documents. Results: In this second year of community service program, Disaster Management Plan (RPB) Documents and Disaster Contingency Plan (RKB) documents were produced. Conclusion: The next community service program should be able to implement similar community service programs to massively empower the Destana program, especially for Destana in various villages that will transform from Pratama to Madya or Utama.